Análisis de vulnerabilidad de la red wifi, del Departamento de TICS del GAD Municipal del cantón Baba - Salinas Valencia, Fabricio Antonio (2021)
In this degree work, a feasibility study is carried out with the objective of analyzing the wireless network of the cantonal GAD of the city of BABA. Wireless connectivity networks are used in various environments, such as corporate, business premises, and family, which may offer not so good service when browsing, causing a bad experience for those who handle digital information, which is why it is necessary have an optimal connection, having as the main factor vulnerability and inconveniences that connection networks present. In order to reach an optimal resolution of this case study, interviews were conducted with the personnel of the municipal GAD of the Baba canton in several departments, including the TICS, who stated that the problems that the networks currently present in the municipality are due to of the lack of maintenance, that they detect if the network has some type of vulnerability, or if a data flow with more bandwidth is required for the institution. The methodology implemented in this case study was inductive in order to identify the vulnerabilities that allow the malfunctioning of the networks, the observation technique was used to determine if the institution's teams correctly execute the security standards of the networks. Wi-Fi networks by performing a scan to determine the Inssider, threats, vulnerabilities and speed of the network with the Nessus tool.